Density Functional Theory Investigation Of Electronic Structure And Muonium Hyperfine Interaction Of 12mer Single Strand Guanine Oligomer - Zaharim, Wan Nurfadhilah (2019)
The aims of this study are to determine the stable muon sites in 12mer single strand guanine (12mer ssG) oligomer, and to determine the associated muonium (Mu) hyperfine coupling constants. The Density Functional Theory (DFT) quantum mechanical method was employed to achived the goals of the study. High-resolution transmission electron microscopy (HRTEM) and UV-visible (UV-Vis) measurements were made to examine the physical structure and the HOMO-LUMO gap of the studied system. Computational investigation was first performed on isolated guanine (isolated G), guanine nucleobase (G nucleobase), and guanine nucleotide (G nucleotide). The C8 Mu trapping site was found to be the most energetically stable in all three molecules. The calculated Fermi contact coupling constants (FCCC) are 337.4 MHz, 334.3 MHz, and 310.6 MHz.